Measuring in the Renaissance an introduction - Lugli, Emanuele 1979- (Cambridge University Press, 2023)
"During the Renaissance, measuring played a critical role in shaping trade, material production (ranging from architecture to tailoring), warfare, legal studies, and even our understanding of the heavens and hell. This Element delves into the applications of measuring, with a particular emphasis on the Italian states, and traces its wide-ranging cultural effects. The homogenization of measurements was endorsed as a means to achieve political unity. The careful retrieval of ancient standards instilled a sense of connection and ownership toward the past. Surveying was fundamental in the process of establishing colonies. This Element not only examines the perceived advantages of measuring, but it also highlights the overlooked distorting aspect of this activity. Measuring was not just a neutral quantification process but also a creative one. By suppressing or emphasizing information about the material world, measuring influenced people's perceptions and shaped their ideas about what was possible and what could be accomplished"--
Literaturverzeichnis Seite 77-100
Keywords: Geschichte 1400-1600; Waage; Längeneinheit; Vermessung; Maßeinheit; Messbarkeit; Messung; Italien; Measurement / History; Science, Renaissance